Pathophysiology Altered Physiological States - Gaze, David C. (IntechOpen, 2018)
Pathophysiology is the convergence of pathology (the discipline of observed changes in a diseased state) with physiology (the mechanisms of systems operation). It represents the functional changes that occur because of injury or disease. This volume provides state-of-the-art up-to-date literature reviews on pathophysiological processes in a number of disease states. The book is organised methodically in a head-to-toe systems approach examining aspects of neuropathophysiology, endocrine pathophysiology, structural biology, renal pathophysiology and genitourinary pathophysiology. This short volume on pathophysiology is intended for general medical and biomedical students at both undergraduate and postgraduate levels. In addition, it is a useful short update of recent advances in research and translational biology to those working in academia or healthcare science.